Spawning behavior, female reproductive potential and breeding technique optimize of threadfin rainbowfish Iriatherina werneri - Muh. Herjayanto; Odang Carman; Dinar Tri Soelistyowati (Jurnal Iktiologi Indonesia, 2016)
Basic information of threadfin rainbowfish especially their reproduction in captivity is little known. Therefore, study on the spawning behaviour and female reproductive potential based on the different treatment of feed (commercial food and natural food) and optimize breeding technique is needed. The study on optimize breeding technique including the effect of different spawning systems (masse or individual), sex ratio (1:1, 1:2 and 1:3), and female size (small, medium and large) to support threadfin rainbowfish culture. The result showed that the threadfin rainbowfish spawn at 13-15 hours after pairing broodfish and the fertilization starts when male spread out and shrink up the fins. The eggs were released faster in the masse than in individual spawing systems and the eggs were released more simultaneously in the morning (94.92%). The threadfin rainbowfish is a partial spawner that spawns every day until 30 days. The potential of eggs and larvae production could be increased up to 4 and 14 times by fed the fish with natural food. Technique for optimize the breeding is using the masse spawning system with sex ratio 1:3 and size range of female is 26.98 to 35.76 mm. Abstrak Informasi reproduksi ikan pelangi Iriatherina werneri pada wadah terkontrol masih sedikit diketahui. Oleh karena itu, diperlukan kajian mengenai tingkah laku memijah, potensi reproduksi ikan betina berdasarkan perbedaan pakan (buatan dan alami), dan optimasi teknik pemijahan. Kajian optimasi pemijahan meliputi pengamatan pengaruh perbedaan sistem pemijahan (massal atau individual), perbedaan rasio kelamin pemijahan jantan : betina (1:1, 1:2, dan 1:3), serta perbedaan ukuran betina (kecil, sedang, dan besar) untuk mendukung kegiatan budi daya. Hasil penelitian menunjukkan bah-wa pemijahan ikan pelangi terjadi pada 13-15 jam sejak pemasangan ikan jantan dan betina yang diawali oleh gerakan ikan jantan mengembangkan dan menguncupkan sirip. Telur yang dikeluarkan pada pemijahan massal berakhir dua jam lebih cepat dibandingkan pemijahan individual dan telur lebih serempak dikeluarkan pagi hari (94,92%). Ikan pelangi merupakan pemijah bertahap yang mampu memijah setiap hari selama 30 hari. Potensi jumlah telur dan larva yang di-hasilkan seekor betina dapat ditingkatkan masing-masing sebanyak empat kali lipat dan 14 kali lipat melalui pemberian pakan alami. Optimasi teknik pemijahan I. werneri dicapai dengan menggunakan sistem massal dengan rasio kelamin 1: 3 dan menggunakan ikan betina berukuran 26,98-35,76 mm.